Comparison of urinary extracellular vesicle isolation methods for transcriptomic biomarker research in diabetic kidney disease. Issue 2 (7th January 2021) - Barreiro, Karina; Dwivedi, Om Prakash; Leparc, German; Rolser, Marcel; Delic, Denis; Forsblom, Carol; Groop, Per‐Henrik; Groop, Leif; Huber, Tobias B.; Puhka, Maija; Holthofer, Harry
Abstract: Urinary Extracellular Vesicles (uEV) have emerged as a source for biomarkers of kidney damage, holding potential to replace the conventional invasive techniques including kidney biopsy. However, comprehensive studies characterizing uEV isolation methods with patient samples are rare. Here we compared performance of three established uEV isolation workflows for their subsequent use in transcriptomics analysis for biomarker discovery in diabetic kidney disease. We collected urine samples from individuals with type 1 diabetes with macroalbuminuria and healthy controls. We isolated uEV by Hydrostatic Filtration Dialysis (HFD), ultracentrifugation (UC), and a commercial kit‐ based isolation method (NG), each with different established urine clearing steps. Purified EVs were analysed by electron microscopy, nanoparticle tracking analysis, and Western blotting. Isolated RNAs were subjected to miRNA and RNA sequencing. HFD and UC samples showed close similarities based on mRNA sequencing data. NG samples had a lower number of reads and different mRNA content compared to HFD or UC. For miRNA sequencing data, satisfactory miRNA counts were obtained by all methods, but miRNA contents differed slightly. This suggests that the isolation workflows enrich specific subpopulations of miRNA‐rich uEV preparation components. Our data shows that HFD, UC and the kit‐based method are suitable methods to isolate uEV for miRNA‐seq. However, only HFD and UC were suitable for mRNA‐seq in our settings.